El análisis financiero en la toma de decisiones y su impacto en la empresa Larvmar S.A. (2022-2023) - Burgos Aguilar, Kerly Yamileth (Machala : Universidad Técnica de Machala, 2024)
The lack of knowledge in financial analysis at LARVMAR S.A. during the 2022-2023 period has negatively impacted the company, leading to poorly informed decision-making. The absence of expertise in applying financial ratios has hindered management’s ability to accurately assess the company’s financial situation. As a result, the organization has struggled to identify areas for improvement, optimize resources, and address potential financial risks, limiting its growth opportunities. Currently, the company's financial analysis relies on basic evaluations of sales reports, expenses, and balance sheets, without applying essential financial indicators. This has affected decision-making, as the lack of detailed profitability and liquidity assessments prevents a deeper understanding of the company’s financial health. The implementation of financial ratios in LARVMAR S.A.'s financial statements for 2022-2023 has revealed strong profitability and liquidity. However, the company does not fully leverage its assets to maximize benefits. To improve future decision-making, it is crucial to adopt a more rigorous financial analysis approach, incorporating key financial indicators to gain a comprehensive understanding of its economic situation.
El análisis financiero en LARVMAR S.A. durante los períodos 2022-2023 ha sido deficiente debido a la falta de conocimiento en técnicas especializadas, lo que ha afectado la toma de decisiones estratégicas y el crecimiento de la empresa. La ausencia de indicadores financieros en la evaluación de los estados contables ha limitado la capacidad de la gerencia para identificar oportunidades de mejora y optimizar los recursos disponibles. Los procedimientos actuales se centran en el análisis básico de informes financieros sin el uso de herramientas clave, lo que ha dificultado una interpretación detallada de la rentabilidad y liquidez. Esto ha llevado a decisiones poco informadas que impactan negativamente en la estabilidad económica de la compañía. Al aplicar ratios financieras, se ha evidenciado que, aunque la empresa mantiene una rentabilidad y liquidez operativa favorables, no maximiza el uso de sus activos para generar mayores beneficios. Se recomienda la implementación de un análisis financiero más riguroso con herramientas avanzadas que permitan evaluar con mayor precisión la situación económica y mejorar la eficiencia operativa. Esto facilitará una gestión más efectiva y contribuirá al crecimiento sostenible de la organización.
Keywords: ANÁLISIS FINANCIERO; TOMA DE DECISIONES; RENTABILIDAD; LIQUIDEZ